2022
DOI: 10.3390/foods11101401
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Microbiota and Their Manipulation for Improved Growth and Performance in Chickens

Abstract: The gut of warm-blooded animals is colonized by microbes possibly constituting at least 100 times more genetic material of microbial cells than that of the somatic cells of the host. These microbes have a profound effect on several physiological functions ranging from energy metabolism to the immune response of the host, particularly those associated with the gut immune system. The gut of a newly hatched chick is typically sterile but is rapidly colonized by microbes in the environment, undergoing cycles of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 262 publications
2
35
0
1
Order By: Relevance
“…Probiotics are defined as “live microbial feed supplements which, when administered in adequate amounts, beneficially affect the host animal by improving the gut microbial balance” [ 179 ]. The proposed modes of action of probiotics are: (1) competitive exclusion and antagonism, (2) improving the host intestinal health and integrity, (3) improving digestion and absorption, (4) enhancing growth and performance, and (5) immunomodulation [ 180 ]. An ideal probiotic should be non-pathogenic, of host origin, free of adverse side effects, should have demonstrated a beneficial effect on the host, be resistant to gastric acid and bile salts, be able to adhere to the host gastrointestinal mucosa, competitively exclude pathogenic bacterial colonization, be sensitive to antibiotics, positively modulate host immune functions, and be able to withstand processing and storage conditions [ 181 , 182 , 183 ].…”
Section: Control Of Necrotic Enteritis In the Post-antibiotic Eramentioning
confidence: 99%
“…Probiotics are defined as “live microbial feed supplements which, when administered in adequate amounts, beneficially affect the host animal by improving the gut microbial balance” [ 179 ]. The proposed modes of action of probiotics are: (1) competitive exclusion and antagonism, (2) improving the host intestinal health and integrity, (3) improving digestion and absorption, (4) enhancing growth and performance, and (5) immunomodulation [ 180 ]. An ideal probiotic should be non-pathogenic, of host origin, free of adverse side effects, should have demonstrated a beneficial effect on the host, be resistant to gastric acid and bile salts, be able to adhere to the host gastrointestinal mucosa, competitively exclude pathogenic bacterial colonization, be sensitive to antibiotics, positively modulate host immune functions, and be able to withstand processing and storage conditions [ 181 , 182 , 183 ].…”
Section: Control Of Necrotic Enteritis In the Post-antibiotic Eramentioning
confidence: 99%
“…The gastrointestinal tract of poultry species is highly populated with microorganisms that exist in a symbiotic relationship with the host [ 1 ]. These complex microbial communities benefit the host by regulating digestion and synthesizing bile acids, vitamins, and short-chain fatty acids [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbial homeostasis was required for the development and maturation of the animals, which affected a wide range of physiology aspects, including growth performance, production performance, nutrient digestibility, immune function, and antioxidative capacity ( Sommer and Bäckhed, 2013 ; Fathima et al, 2022 ). Previous literature reported that RE had the potential to reshape the gut microflora in mice under stressed conditions ( Guo et al, 2018 ; He et al, 2022 ), and rosemary leaf meal could increase the population of Lactobacillus but reduce the population of E. coli and Salmonella ( Ogwuegbu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%